The Effect of Adding Banana Fibers on the Physical and Mechanical Properties of Mortar for Paving Block Applications - Ginan Al-Massri; Hassan Ghanem; Jamal Khatib; Samer El-Zahab; Adel Elkordi (Ceramics)
Paving blocks might encounter diverse environmental conditions during their lifespan. The durability of paving blocks is determined by their capacity to endure various exposure conditions. Synthetic fibers have been used in mortar and concrete to improve their properties. This research investigates the influence of including banana fiber (BF) on the physical and mechanical characteristics of mortar. Five different mortar mixes were developed, with varying amounts of BF ranging from 0 to 2% by volume. Testing included ultrasonic pulse velocity, compressive strength, flexural strength, total water absorption, and sorptivity. Specimens were cured for up to 90 days. The results indicate that using 0.5% BF resulted in an improvement in compressive and flexural strength compared to the control mix. There was an increase in total water absorption and the water absorption coefficient in the presence of fibers. There appeared to be good correlations between the compressive strength and the other properties examined.